Exploring the present discourse on the Early Church Fathers’ teachings on poverty in order to develop proposals for the Johannesburg church’s engagement with the poor - Van Niekerk, A.S. (Attie) (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2011.